A man for all seasons - Zinnemann, Fred, 1907-1997.; Bolt, Robert; Hiller, Wendy, 1912-2003.; McKern, Leo, 1920-2002.; Shaw, Robert, 1927-1978.; Welles, Orson, 1915-1985.; York, Susannah; Scofield, Paul, 1922-2008.; Davenport, Nigel; Hurt, John, 1940-2017.; Redgrave, Corin; Blakely, Colin; et al. (Culver City, CA : Sony Pictures Home Entertainment, 2006)
Sir Thomas More, Chancellor of England, has an unquestioning faith. As a devout Catholic, More refuses to support King Henry VIII's divorce from Catherine of Aragon. In quest of a son, Henry wants to marry his mistress, Anne Boleyn. When the petulant king breaks with Rome and the Pope, More resigns his chancellorship in protest. Unsure in his new position as head of the Church of England, the king is unnerved by More's continued refusal to acknowledge his suzerainty. For his stubborn convictions, More ends up imprisoned in the Tower of London. For holding devotion to God and the Church dearer than his loyalty to the King, More dies.
Start -- Butcher's summons -- With the Cardinal -- Petitions -- Home to Chelsea -- Saying "No" to a heretic -- Duke of Norfolk -- New Lord Chancellor -- "Surprise" visit -- Quiet words -- Catching the tide -- Bad, dangerous spy -- Rich & the new secretary -- King's answer -- More resigns -- Explaining his decision -- King's wedding day -- Letter -- Conversation with Cromwell -- Ending a friendship -- News of the oath -- In the tower -- Inquiry -- Family visit -- Trial -- Richard Rich testifies -- Verdict & Discharge -- Sentence carried out.
DVD; Region 1; Dolby Digital 5.1 or mono; anamorphic widescreen presentation, 1.66:1 aspect ratio.
In English or dubbed French with optional subtitles in English, French, or Portuguese; closed-captioned.
From the play by Robert Bolt.
Wendy Hiller (Alice More), Leo McKern (Cromwell), Robert Shaw (Henry VIII), Orson Welles (Cardinal Wolsey), Susannah York (Margaret More), Paul Scofield (Thomas More), Nigel Davenport (Duke of Norfolk), John Hurt (Rich), Corin Redgrave (Roper), Colin Blakely (Matthew), Cyril Luckham (Archbishop Cranmer).
Photographed byTed Moore ; editor, Ralph Kemplen ; production designer, John Box ; costume design, Elizabeth Haffenden, Joan Bridge ; art director, Terence Marsh ; music composed and conducted by Georges Delerue.
Originally produced as a motion picture in 1966.
Keywords: Henry -- VIII, -- King of England, -- 1491-1547 -- Drama; Anne Boleyn, -- Queen, consort of Henry VIII, King of England, -- 1507-1536 -- Drama; More, Thomas, -- Saint, -- 1478-1535 -- Drama; Divorce -- Religious aspects -- Catholic Church -- Drama; Church and state -- England -- Catholic Church -- Drama; Christian saints -- Drama; Kings and rulers -- Drama; Loyalty -- Drama; Great Britain -- Kings and rulers -- Drama; Great Britain -- History -- Henry VIII, 1509-1547 -- Drama; England -- Social life and customs -- 16th century -- Drama; Bolt, Robert -- Film adaptations; More, Thomas, -- Sir, Saint, -- 1478-1535 -- Drama; Henry -- VIII, -- King of England, -- 1491-1547 -- Drama; Anne Boleyn, -- Queen, consort of Henry VIII, King of England, -- 1507-1536 -- Drama; Divorce -- Religious aspects -- Drama; Church and state -- England -- Drama; Church and state -- Catholic Church -- England -- Drama; England -- Drama; Feature films; Historical films; Historical films; Biographical films; Feature films; Fiction films; Film adaptations; Video recordings for the hearing impaired; Historical -- Feature